Characterization and Genomic Analysis of BUCT549, a Novel Bacteriophage Infecting Vibrio alginolyticus With Flagella as Receptor - Li, Jing; Tian, Fengjuan; Hu, Yunjia; Lin, Wei; Liu, Yujie; Zhao, Feiyang; Ren, Huiying; Pan, Qiang; Shi, Taoxing; Tong, Yigang (Frontiers in Microbiology, 2021)
Vibrio alginolyticus is one of the most important of pathogens that can infect humans and a variety of aquatic animals, which can cause food poisoning and septicemia in humans. Widely used antibiotics are gradually losing their usefulness, and phages are gained more attention as new antibacterial strategies. In order to have more potential strategies for controlling pathogenic bacteria, we isolated a novel V. alginolyticus phage BUCT549 from seafood market sewage. It was classified as a new member of family Siphoviridae by transmission electron microscopy and phylogenetic tree. We propose to create a new genus for BUCT549 based on the intergenomic similarities (maximum is 56%) obtained from VIRIDIC calculations. Phage BUCT549 could be used for phage therapy due to its stability in a wide pH (3.0-11.0) range and high temperature (up to 60°C) environment. It had the latent period of 30-40 mins and the burst size of 141 PFU/infected bacterium. In the phylogenetic tree based on terminase large subunit, BUCT549 was closely related to eight Vibrio phages with different species of host. Meanwhile, our experiments proved that BUCT549 have the ability to infect a strain of Vibrio parahaemolyticus. Co-evolution experiment determined that three strains of tolerant V. alginolyticus evaded phage infestation by mutating the MSHA-related membrane protein expression genes which caused the loss of flagellum. This research on the novel phage identification and the mechanism of infestation will help phages to become an integral part of strategy for biological control agent.